Attitudes of primary school teachers toward inclusion of students with different disabilities - Chichevska Jovanova, Natasha; Rashikj Canevska, Olivera (Издательство Южного федерального университета, Ростов-на-Дону / Таганрог, 2020)
Inclusive education can be defined as an education system that includes all students, and welcomes and supports them to learn, whoever they are and whatever their abilities or requirements. Inclusive education involves transforming the whole education system – legislation and policy, systems for financing, administration, design, delivery and monitoring of education, and the way schools are organized. Positive teacher attitudes are essential for success when children with special educational needs (SEN) are placed into mainstream classrooms. According to the new low for full inclusion in the education system of the Republic of Macedonia, the main goal of our study was to determinate the attitudes of teachers in regular primary school towards inclusion of children with different types of disabilities. 100 teachers in primary school from the city of Skopje were inquired with the teacher inclusion attitudes questionnaire. Data analysis indicates that in general teachers have positive attitudes toward inclusion, but can be noticed that they have a divided opinion on the degree and type of disability. Since inclusion requires constant amendment of practice and development of new teaching strategies and skills, it is essential to offer intensive, systematic, and ongoing staff development to future teachers and practicing teachers.
Keywords: inclusion, attitudes, primary school teachers, disabilities